Between-Person Disparities in the Progression of Late-Life Well-Being - Denis Gerstorf; Nilam Ram; Elizabeth Fauth; Jürgen Schupp; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Throughout adulthood and old age, levels of well-being appear to remain relatively stable. In this chapter, we argue that focusing on a phase of life during which this positive picture does not necessarily prevail promises to help us better understand between-person disparities in the progression of late-life well-being. In a first step, we review empirical evidence from the German Socio-Economic Panel and other large-scale longitudinal data sets to demonstrate that ubiquitous reports of a "stability-despite-loss phenomenon" of well-being do not generalize into years of life immediately preceding death. Instead, mean-level representations of the end of life are characterized by a rapid deterioration in well-being. In a second step, we highlight the vast heterogeneity in how people experience the last years and consider the role of biopsychosocial individual difference factors to account for such disparities. The select factors reviewed here include socio-demographic characteristics, cognitive fitness, pathology, and disability. In a third step, we argue that macro-contextual factors such as the social, service, and physical characteristics of the communities and societies people are living and dying in also profoundly shape the nature and progression of individual late-life well-being. Our conceptual reasoning forecasts some of the insights that can be gained by pursuing this line of research, but also underscores the challenges researchers must deal with.
Keywords: I12; I31; Y8; 330; Late-Life Well-Being; SOEP; BHPS; HRS